(untitled) (Bangladesh Journal of Medical Science, 2021)
Context:Skeletal injuries discovered from human remains are classified into antemortem,perimortem and postmortem. Studies that documents injuries of various skeletal elementsis of vital importance to forensic anthropologist. Aim: This study investigated antemortem,perimortem, postmortem and other injuries caused by various instruments among skeletal elements. Methodology: A total of 200 bones of unknown age and gender were studied.Injuries were interpreted based on basic features specific to them and each was described andphotographed. Chisquare test was used to show association between skeletal elements andtime of injuries. Statistical evaluation was done using SPSS 20 Software Version. Significance was accepted at p<0.05. Result: The bones from this study showed 17.50% antemortem, 24%perimortemand 57% postmortem. Findings showed that 49.50% of the bones had blunt forceinjury, 30.50% had sharp force while 20.00% had ballistic injuries. Basic features of antemorteminjuries were smooth and round fractured edges within bones. Sharp, smooth fractured edgeswere observed among perimortem bones in contrast to irregular, blunt fractured edges anduneven discoloration in postmortem bones .Straight line incisions were seen in bones withsharp force injuries,presence of an entrance wound in ballistic injuries while an impact area wasdiscovered in most bones with blunt force injury.Findings showed that there exist a significantassociation between ante, peri and postmortem injuries in the ulnar,radius and femur bones(X2=25.32;13.35;10.11. p=0.000;0.001,0.006) Conclusion: Bones from this study showed morepost mortem blunt force injury. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.50-57